PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATA PELAJARAN SISTEM KELISTRIKAN - Faizal Widyanto; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aimed to improve: (1) learning activeness and (2) learning achievement of electrical system subject by using demonstration teaching method. The type of this study was an action research. The research subject was the twelveth grade students of SMK Muhammadiyah 1 Bambanglipuro in academic year 2016/2017, while the subject was learning activeness and learning achievement. The research was held on July 2016 by using three cycles. The research instruments were observation guideline and test. The test validity used conctrutc validity. Data analysis techniques used descriptive analysis and quantitative to know the percentage of learning activeness and learning achievement. This study shows that (1) the use of demonstration could improve learning activeness. The percentage of learning activeness in pre cycle was 64.84%, improved in cycle I was 74.38%, cycle II was 74.38%, and cycle III was 88.29%. (2) The use of demonstration could improve learning achievement of electrical system subject. The mean score of learning achievement of pre cycle was 54.84 with 5 students (15.62%) who were completed in learning, cycle I was 70.78 with 10 students (31.25%) who were completed in learning, cycle II was 74.53 with 22 students (68.75%) who were completed in learning, and cycle III was 78.59 with 27 students (84.4%) who were completed in learning.Â